Prosper, consume and be saved. (April 2013) - Maddox, Marion
A Sydney-based megachurch with global reach, well-known for its "prosperity gospel" of financial acquisition, has developed an additional strand: a detailed theology of consumption. The affinity between a theology of guilt-free—indeed, obligatory—consumption and late capitalism goes some way towards explaining the attraction this minority strand of Christianity holds for politicians, including those without personal religious commitments, in a secular electorate.